The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1161/01.atv.0000229694.97827.38
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Risk for Ischemic and Hemorrhagic Stroke

Abstract: Objective-We performed an association study to identify gene polymorphisms for assessing the genetic risk of ischemic or hemorrhagic stroke. Methods and Results-The study population comprised 3151 unrelated Japanese individuals: 1141 stroke patients (636 with atherothrombotic cerebral infarction, 282 with intracerebral hemorrhage, and 223 with subarachnoid hemorrhage) and 2010 controls. The genotypes for 202 polymorphisms of 152 genes were determined by suspension array technology. Multivariable logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
69
1
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 33 publications
(28 reference statements)
9
69
1
4
Order By: Relevance
“…We found that the IL-6 rs1800796 TT genotype was greatly associated with risk of ischemic stroke, and that the IL-6 rs1800795 CC genotype was marginally associated with risk of ischemic stroke. Our finding is consistent with previous studies conducted in Chinese, Japanese, American, and British populations (Humphries et al, 2001;Yamada et al, 2006;Podgoreanu et al, 2006;Tong et al, 2010). This finding suggests that in individuals carrying the TT genotype of IL-6 rs1800796, IL-6 transcription can be influenced through a complex interaction, and a previous study indicated that the T allele of rs1800796 was associated with increased transcription efficiency of IL-6 (Terry et al, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…We found that the IL-6 rs1800796 TT genotype was greatly associated with risk of ischemic stroke, and that the IL-6 rs1800795 CC genotype was marginally associated with risk of ischemic stroke. Our finding is consistent with previous studies conducted in Chinese, Japanese, American, and British populations (Humphries et al, 2001;Yamada et al, 2006;Podgoreanu et al, 2006;Tong et al, 2010). This finding suggests that in individuals carrying the TT genotype of IL-6 rs1800796, IL-6 transcription can be influenced through a complex interaction, and a previous study indicated that the T allele of rs1800796 was associated with increased transcription efficiency of IL-6 (Terry et al, 2000).…”
Section: Discussionsupporting
confidence: 92%
“…With the use of public databases, including PubMed (NCBI) and Online Mendelian Inheritance in Man (NCBI), we selected 202 candidate genes that have been characterized and suggested to be associated with atherothrombotic cerebral infarction. On the basis of published studies or by searching PubMed and single nucleotide polymorphism (SNP) databases [dbSNP (NCBI) and Japanese SNP database (JSNP)], we further selected 296 polymorphisms of these genes, most located in the promoter region or exons, that might be expected to result in changes in the function or expression of the encoded protein (14,15). Wild-type and variant alleles of the polymorphisms were determined from the original sources.…”
Section: Methodsmentioning
confidence: 99%
“…The 150 polymorphisms examined in the present study (data not shown) were selected by genome-wide association studies of ischemic stroke and myocardial infarction (P-value for allele frequency <1.0x10 -7 ) with the use of the GeneChip Human Mapping 500K Array Set (Affymetrix, Santa Clara, CA) (10). We have not examined the relation of these polymorphisms to intracerebral or subarachnoid hemorrhage among Japanese individuals in our previous study (8,9).…”
Section: Selection Of Polymorphismsmentioning
confidence: 95%
“…We previously showed that several gene polymorphisms were associated with intracerebral or subarachnoid hemorrhage in Japanese individuals (7,8). To further examine the genetic factors for these conditions, we have performed an association study for 150 polymorphisms of 144 candidate genes and intracerebral or subarachnoid hemorrhage in 4,304 Japanese individuals.…”
Section: Introductionmentioning
confidence: 99%